2021
DOI: 10.1002/cnm.3526
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics coupling numerical simulation of flow‐diverting stents in the treatment of patients with pulsatile tinnitus

Abstract: Patients with pulsatile tinnitus (PT) have unstable treatment effects after resurfacing surgery. Flow‐diverting stents (FDS) are proposed as a potential method for the treatment of PT, but the therapeutic effect is not clear. This study aimed to investigate the efficacy of FDS in the treatment of patients with PT induced by sigmoid sinus diverticulum (SSD) and sigmoid sinus wall dehiscence (SSWD). In addition, we aimed to explore the treatment mechanism of PT. Transient‐state multiphysics coupling numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
4
13
0
Order By: Relevance
“…A larger amplitude of the flow sound was detected at segments with a higher flow velocity and pressure gradient. This finding substantiates the therapeutic effect of endoluminal TSS stenting, which targets the reduction of regional flow velocity and relief of the trans -stenotic pressure gradient ( Mu et al, 2021a ). Previous computational studies found that the flow-induced displacement of the vascular wall could generate vibro-acoustic noise from 48.76 to 116.57 dB ( Tian et al, 2017 ; Mu et al, 2021a , b ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A larger amplitude of the flow sound was detected at segments with a higher flow velocity and pressure gradient. This finding substantiates the therapeutic effect of endoluminal TSS stenting, which targets the reduction of regional flow velocity and relief of the trans -stenotic pressure gradient ( Mu et al, 2021a ). Previous computational studies found that the flow-induced displacement of the vascular wall could generate vibro-acoustic noise from 48.76 to 116.57 dB ( Tian et al, 2017 ; Mu et al, 2021a , b ).…”
Section: Discussionsupporting
confidence: 77%
“…This finding substantiates the therapeutic effect of endoluminal TSS stenting, which targets the reduction of regional flow velocity and relief of the trans -stenotic pressure gradient ( Mu et al, 2021a ). Previous computational studies found that the flow-induced displacement of the vascular wall could generate vibro-acoustic noise from 48.76 to 116.57 dB ( Tian et al, 2017 ; Mu et al, 2021a , b ). The amplitude of the vibro-acoustic sound surpassed that of the hydroacoustic source when the volume and surface contributions were juxtaposed ( Hsieh et al, 2022 ).…”
Section: Discussionsupporting
confidence: 77%
“…According to the current in vivo displacement sensing results, the major frequency of flow-induced vascular displacement was below the audible frequency range. This outcome contradicts the current coupled CFD outcomes and a few in vitro/computational studies (Tian et al, 2019;Mu et al, 2021). There are two plausible reasons for this divergence: first, the sigmoid sinus vascular wall is tightly fixated onto the concave surface of the sigmoid plate connected by the dura mater situated in between, which can be difficult to reproduce using experimental and computational methods.…”
Section: Vibroacoustic and Hydroacoustic Sources Of Ptmentioning
confidence: 89%
“…As the sound wave pressure dampens due to surrounding human anatomical structures, the acquisition of the absolute amplitude of PT in vivo can be rather arduous. However, the coupled computational fluid dynamics (CFD) technique has recently succeeded in revealing hydroacoustic and flow fluid-structure interaction details of PT but requires accurate establishment of boundary conditions (Tian et al, 2017;Hsieh Y.-L. et al, 2021;Mu et al, 2021). Therefore, continuous refinements on applying in vivo sensed mechanical characteristics of realistic anatomical structures and biomaterials are warranted, to support computational simulations and quantitatively verify surgical efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation